Is lateral entry beneficial to elite swimmers? A preliminary study - Chen, C.; Gao, J.; Bacic, B.; Zhou, S. (ISBS Proceedings Archive (Michigan), 2023)
The purpose of this study was to improve performance of elite swimmers during the starting phase, by analysing whether the lateral entry technique is beneficial to athletes' starting. Participants` (N=12) motion data were obtained from a 3D Performance Analysis System (Kistler 9691A1) with three cameras. Extracted 14 parameters were analysed using paired samples t-test. Differences contributing to the lateral entry performance included decrease of both entry angle and maximum depth by 1° and 0.42 m respectively (p<.01), and increase of push force by 0.08 of body weight (p<.01). The preliminary results show that the lateral technique provides a 0.06 s reduction in time to reaching the first 5 m (p<.05) compared to ordinary entry, suggesting performance improvements at start times.